Contribution of the β-ureidopropionase (UPB1) gene alterations to the development of fluoropyrimidine-related toxicity - Fidlerova, Julie; Kleiblova, Petra; Kormunda, Stanislav; Novotny, Jan; Kleibl, Zdenek (Pharmacological reports, 2012)
BACKGROUND: An impairment of the 5-fluorouracil (5-FU) catabolic pathway, represented by alterations in the dihydropyrimidine dehydrogenase (DPYD) gene, is considered a crucial factor contributing to the development of 5-FU-related toxicity. The β-ureidopropionase (BUP1) enzyme catalyzes the final step in the 5-FU catabolic pathway; however, alterations in the UPB1 gene coding for the BUP1 enzyme have not yet been analyzed in fluoropyrimidine (FP)-treated patients suffering from 5-FU-related toxicity. METHODS: We have performed a mutation analysis of the entire coding sequence of UPB1 based on denaturing high-performance liquid chromatography in 113 cancer patients treated by FP-containing regimes. These patients included 67 individuals suffering from severe 5-FU-related toxicity and 46 individuals with excellent tolerance of chemotherapy. RESULTS: Nine UPB1 variants were detected in the subpopulation of patients with severe toxicity, including a novel mutation affecting the coding sequence (c.872_873+11del13). An analysis of UPB1 variants on 5-FU-related toxicity in the population of all analyzed patients revealed an association between the c.-80C>G (rs2070474) variant and gastrointestinal toxicity. A strong positive correlation was found between the carriers of the c.-80 GG genotype and the development of severe (grade 3-4) mucositis (OR = 7.5; 95% CI = 2.60 - 21.60; p = 0.0002). CONCLUSION: Our results suggest that UPB1 variants may contribute to the development of 5-FU-related toxicity in some FP-treated patients; however, the role of UPB1 alterations is probably less significant than that of DPYD alterations.
Keywords: mutace; DNA vazebné proteiny; dospělí; Antimetabolites, Antineoplastic; Genotype; Female; Fluorouracil; transkripční faktory; Adult; ženské pohlaví; lidé; genotyp; Transcription Factors; Mutation; Male; fluoruracil; Aged; protinádorové antimetabolity; DNA-Binding Proteins; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans